Prevalence and risk of spinal pain among physiotherapists in Poland - Glowinski, Sebastian; Bryndal, Aleksandra; Grochulska, Agnieszka (PeerJ, 2021)
Background The purpose of this study was to determine the prevalence, symptoms of, and risk factors for spinal pain in physiotherapists, as well as to analyse the correlation between these factors and the nature of the work, anthropometric features of the respondents, and the level of their physical activity. Methods The study was conducted among 240 physiotherapists (71 male and 169 female) with a mean age of 38.7 years. They were divided into three groups: physical therapy (37), kinesitherapy (158) and massage (45). Physiotherapists were evaluated with a specially designed questionnaire, the postural discomfort chart, the Neck Disability Index (NDI) questionnaire, and the Oswestry Disability Index (ODI) questionnaire. Results The analysis showed a 91.7% incidence of spinal pain in physiotherapists (91.1% for kinesitherapy, 97.3% for physical therapy, and 88.9% for massage). The study revealed that 50.2% of physiotherapists indicated one to five pain episodes in their careers. Most respondents reported pain in the lumbosacral spine (82%) and the cervical spine (67%). Most respondents (58.5%) scored the pain as moderate (VAS scale). Carrying (62.6%) and torso bending (37.4%) were indicated as the causes of pain. Conclusions Physiotherapists demonstrate a high prevalence of spinal pain. Physical activity reduces the frequency of pain episodes.
Keywords: Spinal pain; Physiotherapists; Risk factors; Neck Disability Index; Oswestry Disability Index